2021
DOI: 10.2147/dmso.s288065
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Clinical Trials on Type 2 Diabetes Mellitus: A Comprehensive Analysis of the ClinicalTrials.gov Database

Abstract: A better understanding of the current features of type 2 diabetes mellitus (T2DM)related clinical trials is important for improving designs of clinical trials and identifying neglected areas of research. It was hypothesized that the trial registration policy promoted the designs of T2DM-related trials over the years. Therefore, this study aimed to present a comprehensive overview of T2DM-related clinical trials registered in the ClinicalTrials.gov database. Methods: T2DM-related clinical trials registered in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…A possible explanation for the low proportion of completed studies was that as most of these trials (72.5%) had been performed in the last 4 years, and thus the majority of these trials were still ongoing. Among the completed 26 trials, 16 (61.5%) had reported their results on ClinicalTrials.gov, which was significantly higher than the number of trials on other diseases, such as diabetes, that had reported their results (31,33). The most abundant type of study (more than half of the registered studies; 54.8%) was phase 2 trials, followed by phase 1 trials (17.9%) and phase 1-2 trials (13.2%, Figure 3).…”
Section: General Characteristics Of the Registered Clinical Trialsmentioning
confidence: 89%
See 1 more Smart Citation
“…A possible explanation for the low proportion of completed studies was that as most of these trials (72.5%) had been performed in the last 4 years, and thus the majority of these trials were still ongoing. Among the completed 26 trials, 16 (61.5%) had reported their results on ClinicalTrials.gov, which was significantly higher than the number of trials on other diseases, such as diabetes, that had reported their results (31,33). The most abundant type of study (more than half of the registered studies; 54.8%) was phase 2 trials, followed by phase 1 trials (17.9%) and phase 1-2 trials (13.2%, Figure 3).…”
Section: General Characteristics Of the Registered Clinical Trialsmentioning
confidence: 89%
“…If an industry was listed as the lead funder, the trial was classified as being funded by that industry. If the National Institutes of Health (NIH) was listed as the lead funder, the trial was considered NIH-funded (30,31). According to the recommendations of the American Society for Radiation Oncology (ASTRO), the American Society of Clinical Oncology (ASCO), and the American Urological Association (AUA) evidence-based guidelines, we further classified the RT types into the following three groups according to the radiation fractionation size: conventionally fractionated (1.8-2.0 Gy per fraction), moderately hypofractionated (2.4-3.4 Gy per fraction), and ultra-hypofractionated (5 Gy or more per fraction) (32).…”
Section: Data Extractionmentioning
confidence: 99%
“…[8] Trials with type 2 diabetes mellitus showed a publication rate of less than 40% of completed trials. [9] The reason is that the current pathogenesis of ITP has not been fully elucidated, and some patients with ITP have poor therapeutic effects, which further promotes more positive results in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Primary immune thrombocytopenia (ITP) manifests as peripheral platelets less than 100×10 9 /L, and other causes of thrombocytopenia should be excluded. This disease, also known as idiopathic thrombocytopenic purpura, is an acquired disease that is immunologically mediated.…”
Section: Introductionmentioning
confidence: 99%
“…DM is linked to an elevated risk of numerous types of diseases and malignancies [1]. The disease's prevalence is anticipated to rise to 623 million by 2045, with type 2 diabetes mellitus (T2DM) accounting for about 90% of cases [2]. Hyperglycemia is a symptom of T2DM caused by insulin resistance and a decrease in insulin production.…”
Section: Introductionmentioning
confidence: 99%